Konstitutionalisme Pembuatan Peraturan Daerah Tentang Desa (Analisis Undang-Undang Nomor 3 Tahun 2024 Tentang Perubahan Kedua Atas Undang-Undang Nomor 6 Tahun 2014 Tentang Desa) - Moh. Hudi; Octav Galang Ramadhan (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
Regency regulations are regulations at the district or city level and are crucial. This is because they are a manifestation of Article 1 of the 1945 Constitution, which states that Indonesia is a country based on the rule of law. As a consequence of a state based on the rule of law, one aspect of this is legal certainty, including the requirement for districts to have regional regulations as a means of regulating society and government at the district level. With the enactment of Law No. 3 of 2024 concerning Villages, districts should be able to create regional regulations, as mandated by the constitution, which mandates that lower-level regulations must comply with higher-level regulations. However, there is still debate regarding the creation of regional regulations concerning villages, driven by the lack of a government regulation implementing Law No. 3 of 2024.